Assessment of knowledge, attitude and practices of pharmacovigilance among health care professionals at a tertiary care teaching hospital in Central India - Acharya, Ashvika; Abraham, Jijo Philip (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Adverse drug reactions (ADRs) are a significant cause of morbidity and mortality worldwide and remain substantially underreported. Pharmacovigilance and spontaneous ADR reporting by health care professionals (HCPs) are critical to identify and mitigate drug-related harm. Our study assessed knowledge, attitude and practice (KAP) regarding pharmacovigilance and explored factors underlying ADR underreporting among HCPs at a tertiary teaching hospital in central India. Methods: A cross-sectional questionnaire-based survey was administered via Google forms to 160 consenting HCPs (48 doctors, 112 nurses) at a tertiary care teaching hospital. The instrument contained 15 KAP items (5 knowledge-yes/no; 5 attitude-5-point Likert; 5 practice-yes/no) plus a multiple-option item on causes of underreporting. Pretesting, expert validation and Cronbach’s α (0.773) were done. Descriptive statistics were computed. Results: All doctors (100%) correctly identified ADRs and life-threatening potential; 93.8% recognized that rare ADRs are primarily identified in post-marketing (phase IV) surveillance. Nurses demonstrated high recognition of ADR concept (88.4%) but lower awareness on some specifics (e.g., 67.9% aware that rare ADRs appear in phase IV). Practice differed markedly: while 91.7% of doctors reported routinely encountering ADRs and 89.6% acknowledged ADR documentation, only 16.7% of doctors reported using the covigilance programme of India (PvPI) mobile app; nurses reported substantially lower active reporting behaviours (practice item responses range 6.3-48.2%). Major reasons for underreporting cited were lack of knowledge (doctors 85.4%, nurses 75.0%), difficulty in causality decision (doctors 56.3%, nurses 48.2%), and limited access to reporting forms (doctors 47.9%, nurses 36.6%). Conclusions: HCPs exhibited satisfactory knowledge and positive attitudes but suboptimal reporting practices, especially among nurses. Interventions such as targeted training, simplified reporting pathways, and institutional pharmacovigilance centres are recommended to improve ADR reporting rates.